A novel colorimetric and ratiometric fluoride ion sensor derived from gallic acid. (17th December 2020) - Shi, Heng; Li, Xiangguo; Chen, Hongjin; Xing, Jieni; Zhang, Rui; Liu, Jian
Abstract : We report a novel colorimetric and ratiometric fluoride ion sensor derived from gallic acid. Abstract : A novel colorimetric and ratiometric probe (SH-GA ) for the fluoride ion detection was designed and synthesized from gallic acid. SH-GA exhibited a selective color change from colorless to yellow in the presence of F − among the eight anions (F −, Cl −, Br −, I −, H2 PO4 −, HSO4 −, CH3 COO −, and ClO4 − ), either in THF or DMF solutions. The binding stoichiometry between SH-GA and fluoride ions was determined to be 1 : 1, and the complexation constant was 1.5 × 10 3 M −1 in THF. The detection limit of the SH-GA probe reached as low as around 1 μM in THF. 1 H NMR titration results and DFT calculations suggested a deprotonation process via hydrogen bonding interactions between the fluoride ion and amino group of SH-GA .